Struktur Modal dan Kinerja Perusahaan pada Perusahaan yang Terdaftar di Jakarta Islamic Index - Lisna Oktaviani Ambarwati; Muhamad Umar Mai; Rani Putri Kusuma Dewi (Indonesian Journal of Economics and Management, 2021)
This research proposes to analyze the effect of capital structure on company performance in companies listed in JII for the 2014-2018 period. The company performance is based on the company's accounting performance as measured by ROE and the company's market performance as measured by PBV. Capital structure in this study is measured DAR, DER, and MLEV. The data used is secondary data in the form of companies’ summary report from the Indonesian Capital Market Directory (ICMD). The sample selection used adpurposive samplingnmethod with predetermined criteria. The samples obtained were 16 companies. Data analysis used panel data regression analysis using Eviews 10 software. The results are DER has a positive and significant effect on ROE and PBV, DAR has not a positive and insignificant effect on ROE and PBV. Meanwhile, MLEV has a negative and significant effect on ROE and PBV.